PARADIGMA PENILAIAN KELAS DALAM PERSPEKTIF PERUNDANG-UNDANGAN PENDIDIKAN DI INDONESIA - Tenti Putri Handayani; Juwita Sari Indah, Rahmathul Dilfa; Wahyuni Safitri, Adriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the classroom assessment paradigm from the perspective of educational legislation in Indonesia, focusing on policy changes and their implementation in the context of the 2013 Curriculum and the Merdeka Curriculum. The method used is literature review (library research), analyzing various regulations, policy documents, and relevant previous studies. The results indicate that the classroom assessment paradigm in Indonesia has shifted from final exam-based assessments to more holistic and continuous assessments, encompassing cognitive, affective, and psychomotor aspects. Authentic assessment, which measures students' skills in real-world situations through various methods such as project tasks and portfolios, has become the main principle in the new assessment policy. However, significant challenges remain in implementation, particularly regarding the limited understanding and skills of teachers in developing assessment instruments that align with these principles. The implications of this study highlight the importance of developing teachers' capacity through ongoing training to enable them to implement competency-based assessments that comply with existing regulations. Furthermore, the synergy between educational policy and field practices is crucial in realizing a more equitable, objective, and effective assessment system to support the improvement of education quality in Indonesia.